Reading skills promotion: Results on the impact of a preschool intervention - Sucena, Ana; Silva, Ana Filipa; Marques, Cátia (Frontiers in Education, 2023)
There is a strong correlation between preschool education skills such as phonological awareness and language and success in reading and spelling acquisition. Even though this is still not the focus of the early intervention. This study presents the preliminary results of the impact of an intervention program developed to promote reading foundation skills. The study was conducted with 627 children in the last year of preschool education (54.2% boys), ages between 4 years and 10 months and 6 years and one month. Participants were divided into intervention (n=242) and comparative (n=385) group. Language, implicit and explicit phonological awareness, and rime implicit awareness were assessed. The intervention group reached statistically higher values in all dimensions at the post-test, a higher magnitude effect and 80% of these children entered the first-grade overpassing cut-off criteria for reading acquisition difficulties. These results support the impact of the program.